Hi there! :)
Answer:
![\huge\boxed{y = -1/4, 1/2.}](https://img.qammunity.org/2021/formulas/mathematics/college/eho4wjiuh9zoo5pn11qto1rtp3honp700i.png)
Given the equation:
8y² - 2y - 1 = 0
Find two numbers that multiply into -1 and sum up to -2. Remember, the 8 as the leading coefficient must be taken into account.
After guessing and checking, we get:
(4y + 1) (2y - 1) = 0
Use the Zero-Product Property to solve for y:
4y + 1 =
4y = -1
y = -1/4
--------------
2y - 1 = 0
2y = 1
y = 1/2
Therefore, solutions to this equation are:
y = -1/4, 1/2.